The Representation of The Touhoku Disaster in the Movie Shin Gojira - Shafwan, Fauzan Indra; Hermawan, Daniel (KIRYOKU, 2025)
In the year 2011, Japan was faced by a major disaster that affected the Touhoku region. The disaster was the largest natural disaster Japan has ever experienced. In 2016, TOHO Studios released a movie titled Shin Gojira. This movie draws direct inspiration from the 2011 great disaster. This research aims to analyze how the movie Shin Gojira represents the Touhoku disaster in terms of the natural disaster, the Japanese government, and Japanese society. The research was conducted using qualitative methods and the content analysis method. The author also used Roland Barthes’ semiotic theory to analyze the connotation and denotation meanings of the primary data. Based on the results of this study, it can be concluded that in representing natural disasters, the movie Shin Gojira uses Gojira itself to represent the earthquake, tsunami, and Fukushima nuclear reactor disaster. In representing the Japanese government, Shin Gojira criticizes the Japanese government for being unprepared for a disaster, and the complicated government bureaucratic process. In representing Japanese society, Shin Gojira criticizes Japanese citizens who do not obey the rules and exploit a disaster. However, Shin Gojira also represents the trauma of the victims of the 2011 disaster.